The perils of proximity China-Japan security relations - Bush, Richard C. 1947- (Brookings Institution Press, 2010)
"Explores the factors underlying the security dilemma confronting Japan and China despite their positive economic interaction, including China's growing military capability, the Japan-U.S. security alliance, and issues such as Japan's occupation of China in the mid-twentieth century and rights in the East China Sea"--Provided by publisher.